Comparative analysis of word formation systems in English and Uzbek languages - Khudoynazarova , Dildora (The Lingua Spectrum, 2025)
The morphological, syntactic, and semantic structures of the word creation systems in Uzbek and English are compared in this study. Word development exhibits both universal and language-specific characteristics as a basic linguistic process. While Uzbek is an agglutinative language that uses a lot of suffixation, reduplication, and compounding, English, which is primarily an analytical language, depends significantly on affixation, compounding, and conversion. This study finds structural similarities and differences between the two languages by looking at important processes including derivation, inflection, and blending. The analysis emphasizes how word production is influenced by historical development, cultural context, and linguistic typology. To provide a thorough comparison, information was gathered from dictionaries, corpora, and real texts. The results show that although the two languages use similar processes, such as compounding and derivation, Uzbek uses more suffixes and reduplication since it is an agglutinative language. This research advances our knowledge of cross-lingual morphological processes, which has consequences for linguistic theory, translation, and language instruction.